Integrative Informatics Analysis of Transcriptome and Identification of Interacted Genes in the Glomeruli and Tubules in CKD - Liu, Lingyun; Ma, Fuzhe; Hao, Yuanyuan; Yi, Zhengzi; Yu, Xiaoxia; Xu, Bo; Wei, Chengguo; Hu, Jinghai (Frontiers in Medicine, 2021)
Chronic kidney disease (CKD) is a complex disease in which the renal function is compromised chronically. Many studies have indicated crosstalk between tubule and glomerulus in CKD progression. However, our understanding of the interaction of tubule and glomeruli injury remains incomplete. In this study, we applied a meta-analysis approach on transcriptome of tubule and glomeruli of CKD patients to identify differentially expressed genes signature. Functional analysis of pathways and gene ontology found that tubular DEGs mainly involved in cell assembly and remodeling, glomerular DEGs were cell proliferation and apoptosis, overlapping DEGs were mainly immune response. Correlation analysis was performed to identify the associated DEGs in tubule and glomeruli. Secreted protein comparison and verification experiments indicated that WFDC2 from tubule could downregulate PEX19 mRNA and protein levels at glomeruli in diabetic kidney disease (DKD). This study revealed the distinctive pathways of tubule and glomeruli and identified interacted genes during CKD progression.